PREDICTION ENDOMETRIAL CANCER IN WOMEN WITH ENDOMETRIAL HYPERPLASTIC PROCESSES IN PREMENOPAUSAL - A. L. Unanyan; I. S. Sidorova; E. A. Kogan; D. V. Baburin (IRBIS LLC, 2016)
We have identified risk factors and determined their significance and relative risk in endometrial oncotransformation based on mathematical analysis of clinical and anamnestic data and molecular-biological indicators. The structural, functional and molecular mechanisms of hyperplastic processes of endometrium in premenopausal women were investigated based on a complex immunohistochemical studies. Our study revealed the features of the expression of tumor suppressor gene PTEN and the marker of tight junctions Claudin 3 and the proliferation marker Ki-67 in epithelial and stromal components based on morphological variant of the pathological process of the endometrium.We have performed a comparative analysis of clinical, morphological and molecular biological studies and as a result suggested a new approach to the study of endometrial hyperplastic processes in premenopausal women, that helps to detect women with increased risk of endometrial oncopathology and gives opportunity to perform pathogenetically based approach to therapy.